D‐bifunctional protein deficiency caused by splicing variants in a neonate with severe peroxisomal dysfunction and persistent hypoglycemia. Issue 1 (8th October 2021) - Werner, Kelly M.; Cox, Allison J.; Qian, Emily; Jain, Preti; Ji, Weizhen; Tikhonova, Irina; Castaldi, Christopher; Bilguvar, Kaya; Knight, James; Ferdinandusse, Sacha; Fawaz, Rima; Jiang, Yong‐Hui; et al.
Abstract: D ‐bifunctional protein (DBP) deficiency is a rare, autosomal recessive peroxisomal enzyme deficiency resulting in a high burden of morbidity and early mortality. Patients with DBP deficiency resemble those with a severe Zellweger phenotype, with neonatal hypotonia, seizures, craniofacial dysmorphisms, psychomotor delay, deafness, blindness, and death typically within the first 2 years of life, although patients with residual enzyme function can survive longer. The clinical severity of the disease depends on the degree of enzyme deficiency. Loss‐of‐function variants typically result in no residual enzyme activity; however, splice variants may result in protein with residual function. We describe a full‐term newborn presenting with hypotonia, seizures, and unexplained hypoglycemia, who was later found to have rickets at follow up. Rapid whole genome sequencing identified two HSD17B4 variants in trans ; one likely pathogenic variant and one variant of uncertain significance (VUS) located in the polypyrimidine tract of intron 13. To determine the functional consequence of the VUS, we analyzed RNA from the patient's father with RNA‐seq which showed skipping of Exon 14, resulting in a frameshift mutation three amino acids from the new reading frame. This RNA‐seq analysis was correlated with virtually absent enzyme activity, elevated very‐long‐chain fatty acids in fibroblasts, and a clinically severe phenotype. Both variants are reclassified as pathogenic. Due to the clinical spectrum of DBP deficiency, this provides important prognostic information, including early mortality. Furthermore, we add persistent hypoglycemia to the clinical spectrum of the disease, and advocate for the early management of fat‐soluble vitamin deficiencies to reduce complications.